GREEN HUMAN RESOURCE MANAGEMENT PRACTICES AND THEIR IMPACT ON INNOVATIVE BEHAVIOR - Sattar Radhi Abid (Galaxy International Interdisciplinary Research Journal, 2024)
This research aimed to test the impact of green human resource management practices in enhancing the innovation behavior of employees for a sample of faculty members in several private colleges and universities in the Middle Euphrates region. The sample size was (175) professors of various scientific titles. The research adopted the descriptive analytical approach to the data collected through the questionnaire. The research used some statistical tools such as means, standard deviations, and Pearson correlation coefficient, as well as a statistical program (SPSS V.23). The most prominent finding of the research was the direct impact of green human resource management practices on the innovation behavior of employees and the relationship between them. The research also showed the need to spread the green culture by holding panel discussions, seminars, and scientific conferences related to environmental protection and preservation.